RETRACTED: Forecasting the development dynamics of coastal systems utilizing remote sensing data - Protsenko S.V. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001